Evaluating Outcome-Based Education: A Mixed-Methods Assessment of Project-Based Academic Writing in Indonesia - Agus Milu Susetyo; Rusdhianti Wuryaningrum; Nurkamilah Nurkamilah (FKIP Universitas Lampung, 2026)
Outcome-Based Education (OBE) requires appropriate evaluation mechanisms to assess the achievement of Program Learning Outcomes (PLOs) through observable and measurable performance outcomes, ensuring compatibility with Indonesian language pedagogy at the university level. Scientific articles produced by students through project-based learning provide critical evidence of PLO attainment. This study examines students’ achievement of PLOs via scientific articles from the Indonesian Language course, identifies the strongest and weakest competency aspects, and explores implications for project-based Indonesian language learning. An evaluative design employing a mixed-methods approach was used. Quantitative data were collected through rubric-based performance assessments of students’ scientific articles, while qualitative data were obtained through content analysis of the articles, interviews with lecturers, and classroom observations. Descriptive statistics and thematic analysis were applied to analyze the data. The findings indicate an uneven pattern of PLO achievement. Students demonstrate strong performance in the structural aspects of scientific writing and clarity of academic communication (PLO 2), reflecting their ability to adhere to formal academic conventions. However, competencies involving higher-order thinking, particularly critical argumentation and the integration of theory with empirical data (PLO 3), show lower achievement levels. Qualitative data reveal that many student articles emphasize descriptive reporting of results rather than theory-based analysis. These results suggest that Project-Based Learning (PjBL) effectively supports technical writing skills but does not fully develop students’ critical academic reasoning and theoretical synthesis. Therefore, instructional practices should emphasize guided reflection, analytical discussion, and theory–data integration to enhance higher-order academic literacy within the OBE framework. Kata kunci: outcome-based education, program learning outcomes, performance-based assessment, project-based indonesian language learning, scientific articles.